Evaluation of Diagnostic Efficacy of Two Different Microscopic Techniques and Fungal Culture in Onychomycosis - N Subathra (National Journal of Laboratory Medicine, 2017)
Introduction: Onychomycosis is a term used to describe any fungal infection of nail apparatus and is caused mainly by dermatophytes, non-dermatophytic moulds and yeast. Clinical examination based on physical findings alone is not a reliable method of diagnosing onychomycosis. Laboratory diagnosis of fungal nail infection relies on microscopic visualization of fungal cells from the material obtained as well as definitive identification of fungus by culture. Aim: To find out the diagnostic efficacy of two different microscopic techniques and fungal culture in onychomycosis. Materials and Methods: It is a cross-sectional lab based study conducted at Government Tertiary Hospital in Coimbatore district, India, from 85 clinically suspected cases of having fungal nail infections. All nail samples were subjected to routine KOH mount, modified KOH with 40% DMSO (Dimethyl Sulfoxide) and fungal culture on two tubes of Sabouraud’s Dextrose agar with chloramphenicol and cycloheximide/ Sabouraud’s Dextrose agar with chloramphenicol at 37ºC and at 25ºC for 3 weeks. Results: Out of 85 samples, total culture positive cases were 46 (54%) and all the three groups namely dematophytes, non-dermatophytic moulds and yeasts were isolated. Total KOH positive cases were 43 (51%). Conventional microscopy method positivity was 48% and modified microscopy method positivity was 51%. Twenty five cases (29.41%) were negative by both the techniques. The culture and microscopy were equally sensitive (p-value ≥ 0.05) in this study. Two microscopic techniques (KOH alone and modified KOH with DMSO) were also compared. The sensitivity of both the techniques was equal, 50.6% (p = 0.588) and 48.2% respectively. Conclusion: Both microscopy and fungal culture should be considered complementary to each other in diagnosing onychomycosis. The modified KOH with DMSO mount had allowed fastest and better visualization of fungal elements at 10 minutes instead of routine 30 minutes.